PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PESERTA PELATIHAN DASAR CPNS PADA BADAN PENGEMBANGAN SUMBER DAYA MANUSIA PROVINSI SULAWESI TENGGARA - Amalul Syahid (Universitas Halu Oleo, 2022)
This study aims to analyze the effect of service quality on the satisfaction of basic training participants (Latsar) CPNS at the Human Resources Development Agency (BPSDM) of Southeast Sulawesi Province. The research population of all participants of the CPNS group II latsar appointment in 2020 is 40 people, carried out in October - November 2021. The survey research method, total sampling of data is 40 respondents, data collection uses a questionnaire. Research variables, service facilities, evaluation of Widyaiswara, training methods, impact of learning and knowledge for participants as well as satisfaction and changes in participant behavior. Measurement scale, Likert scale. Data analysis using SPSS program. The results of this study in general, respondents were satisfied with the services at the BPSDM of the Province of Southeast Sulawesi, on the contrary, a small proportion reported that they were still dissatisfied. The results of the linear regression test obtained the Adjusted R Square of 0.659 or 65, 9% of respondents' satisfaction level variables could be explained by independent variables and 34.1% was explained by other variables. Maximumservice delivery still needs attention.